Effectiveness of You Tube as an Online Learning Media - Rahmatika, Rahmatika; Yusuf, Munawir; Agung, Leo (Journal of Education Technology, 2021)
Covid 19 pandemic causes the transformation  of  several aspects in Human interaction being limited.Changes also occur in the world of education.The world of education transfroms from  face-to-face into online learning.This study aimed to determine the impact of the Covid 19 pandemic in the world of education, especially at the elementary school level and the effectiveness of You Tube learning media as a solution to the education transformation  due to Covid 19.This research used qualitative research methods with data analysis techniques.The researcher found that the impact of Covid 19 in education, especially primary school children, was the limitations of parents in guiding the learning process because they were busyso that you tube learning media became an alternative learning choice for schools.